2016
DOI: 10.1007/s11104-016-2824-2
|View full text |Cite
|
Sign up to set email alerts
|

Root oxygen loss from Raphia taedigera palms mediates greenhouse gas emissions in lowland neotropical peatlands

Abstract: Aims Little is known about the influence of vegetation on the timing and quantities of greenhouse gas fluxes from lowland Neotropical peatlands to the atmosphere. To address this knowledge gap, we investigated if palm forests moderate greenhouse gas fluxes from tropical peatlands due to radial oxygen loss from roots into the peat matrix. Methods We compared the diurnal pattern of greenhouse gas fluxes from peat monoliths with and without seedlings of Raphia taedigera palm, and monitored the effect of land use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 69 publications
2
25
0
Order By: Relevance
“…Root-derived CO 2 may be further influenced by differences in root exudate composition between species ) and with plant age and developmental stage, which will affect microbial substrate availability (Smith 1976;Aulakh et al 2001), and rates of root oxygen loss which can enhance CH 4 oxidation (Hoyos-Santillan et al 2016a). Differences in C. panamensis and R. taedigera rooting structures have previously been noted with large surface root mats and pneumatophores under R. taedigera, and large buttress roots and a microtopography dominated by knee-roots under C. panamensis, which may account for the observed differences in fluxes (Wright et al 2013b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Root-derived CO 2 may be further influenced by differences in root exudate composition between species ) and with plant age and developmental stage, which will affect microbial substrate availability (Smith 1976;Aulakh et al 2001), and rates of root oxygen loss which can enhance CH 4 oxidation (Hoyos-Santillan et al 2016a). Differences in C. panamensis and R. taedigera rooting structures have previously been noted with large surface root mats and pneumatophores under R. taedigera, and large buttress roots and a microtopography dominated by knee-roots under C. panamensis, which may account for the observed differences in fluxes (Wright et al 2013b).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, plants release root exudates comprising species-specific combinations of sugars, organic acids and amino acids, which represent an additional significant substrate for heterotrophic microbial respiration (Smith 1976;Hanson et al 2000;Girkin et al 2018). A third significant source of CO 2 from anoxic wetlands is the oxidation of CH 4 driven by radial oxygen loss from root systems (Hoyos-Santillan et al 2016a) and aerobic surface peat (Jauhiainen 2005;Wright et al 2013a). Terms applied to describe this combination of processes include ''root-rhizosphere respiration'' (Sayer and Tanner 2010), ''root respiration'' (Andrews et al 1999), ''rhizosphere respiration'', and ''root-derived CO 2 '' (Kuzyakov and Larionova 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Shallow subsurface peat has previously been identified as a dominant source of CH 4 in the profile [18], and our results suggest that substantial oxidation is driven by root oxygen inputs at these depths, because the most substantial reductions in dissolved oxygen following root exclusion were found at 10-15 cm depth (1.6%-2.9%). An ex situ study of R. taedigera seedlings demonstrated that root oxygen can suppress CH 4 fluxes by 40% up to 2 cm from root surfaces and was more pronounced in later growth stages of seedlings, most likely due to the increased spread of root aerenchymateous tissue enhancing the release of oxygen into peat [28]. Similar effects occur during rice development, whereby CH 4 emissions decline in more advanced growth stages due to increased CH 4 oxidation and the inhibition of methanogenesis [29,30].…”
Section: Peat Surface Methane Fluxesmentioning
confidence: 94%
“…Both variables are closely linked, with redox potential, measuring the activity of electrons within the peat, and pH assessing proton activity (Reddy and DeLaune 2008). Redox potential is also closely linked to soil moisture content, as waterlogged soils are low in oxygen, except for inputs derived from root oxygen loss and atmospheric diffusion at the surface boundary (Hoyos-Santillan et al 2016a). Plant root inputs of carbon (root exudates) are also able to directly influence peat properties, and may therefore also exert an indirect control on microbial community structure and function, but the precise effect is dependent on the composition and concentration of the input (Girkin et al 2018b).…”
Section: Environmental Regulation Of Microbial Community Structurementioning
confidence: 99%
“…Plants are key in regulating GHG emissions, as species specific litter inputs define initial peat properties (Cooper et al 2019;Upton et al 2018) and rates of decomposition (Hoyos-Santillan et al 2016b;Hoyos-Santillan et al 2015). Plant inputs of oxygen and carbon, in the form of root exudates, have also been identified as critical regulators (Girkin et al 2018c;Hoyos-Santillan et al 2016a). Water table height and peat temperature are key environmental regulators, with the former determining whether anaerobic or aerobic decomposition pathways dominate, affecting the balance of CO 2 versus CH 4 production, and the latter determining the rate of biological processes (Girkin et al 2020;Hooijer et al 2012;Hooijer et al 2010;Jauhiainen et al 2005).…”
Section: Introductionmentioning
confidence: 99%